2010
DOI: 10.1371/journal.pone.0009017
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cardiac Troponin I in Sepsis and Septic Shock: No Evidence for Thrombus Associated Myocardial Necrosis

Abstract: BackgroundElevated cardiac troponin I (cTnI) is frequently observed in patients with severe sepsis and septic shock. However, the mechanisms underlying cTnI release in these patients are still unknown. To date no data regarding coagulation disturbances as a possible mechanism for cTnI release during sepsis are available.Methodology/Principal FindingsConsecutive patients with systemic inflammatory response syndrome (SIRS), sepsis or septic shock without evidence of an acute coronary syndrome were analyzed. Coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 29 publications
(27 reference statements)
2
42
0
1
Order By: Relevance
“…In addition, Corrales-Medina et al showed recently in a cohort study that 10-30% of adults (without clinical history of cardiac disease) admitted for 16 CAP, developed clinically relevant heart failure, arrhythmias, or acute coronary syndromes, up to 10 years after hospitalization (6-8). More commonly, up to 59% of patients admitted with sepsis develop a cardiac phenomenon called demand ischemia (i.e., mild troponin elevation and repolarization abnormalities in absence of myocardial infarction or coronary disease), rather than sepsis-induced cardiomyopathy or MACE (39)(40)(41). In our study, we found that all six previously healthy NHP with pneumococcal pneumonia, developed nonspecific cardiac changes that cannot be categorized as MACE but are consistent with what clinicians call demand ischemia.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, Corrales-Medina et al showed recently in a cohort study that 10-30% of adults (without clinical history of cardiac disease) admitted for 16 CAP, developed clinically relevant heart failure, arrhythmias, or acute coronary syndromes, up to 10 years after hospitalization (6-8). More commonly, up to 59% of patients admitted with sepsis develop a cardiac phenomenon called demand ischemia (i.e., mild troponin elevation and repolarization abnormalities in absence of myocardial infarction or coronary disease), rather than sepsis-induced cardiomyopathy or MACE (39)(40)(41). In our study, we found that all six previously healthy NHP with pneumococcal pneumonia, developed nonspecific cardiac changes that cannot be categorized as MACE but are consistent with what clinicians call demand ischemia.…”
Section: Discussionsupporting
confidence: 64%
“…Electrocardiography and echocardiography in these patients rarely demonstrate ischemic changes, and few patients have inducible ischemia on stress testing or occlusive coronary thrombus on autopsy 8, 26, 30. Postulated causes for troponin elevations in septic patients include ischemic mechanisms (eg, supply–demand imbalance or microvascular spasm or thrombosis) and nonischemic mechanisms (eg, reversible myocardial membrane leakage of cytosolic TnT pool or direct cellular toxicity from inflammatory mediators, microbial toxins, or excessive catecholamine levels) 7, 31, 32. While relative hypovolemia, inadequate resuscitation, and prolonged hypotension may contribute to myocardial injury in patients with septic shock, fluid resuscitation does not appear to influence the subsequent values of hs‐TnT on serial testing 12…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis can also cause abrupt cardiac arrest through effects independent of coronary ischemia, either through direct arrhythmogenic effects or through nonischemic myocardial injury and circulatory dysfunction. [25][26][27][28][29] While we were not able to investigate these mechanisms directly, we found myocardial ischemia/infarction as a possible cause in 6.3% of arrests in patients with pneumonia, and it was an active diagnosis in 13.4%. These are likely underestimates, as some cases of myocardial ischemia/infarction could have been undetected prior to an IHCA.…”
Section: Discussionmentioning
confidence: 99%